2016
DOI: 10.1111/jcpp.12641
|View full text |Cite
|
Sign up to set email alerts
|

Reduced tract integrity of the model for social communication is a neural substrate of social communication deficits in autism spectrum disorder

Abstract: The tract integrity of the model for social communication is reduced in ASD, and the reduction is associated with impaired social interaction. Our results support that reduced tract integrity of the model for social communication might be a neural substrate of social communication deficits in ASD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
29
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 35 publications
(35 citation statements)
references
References 64 publications
(91 reference statements)
4
29
0
Order By: Relevance
“…Alteration of the FAT was also found in boys with ASD [Lo et al, ]. Consistent with previous reports, the present study found that the boys with ASD showed significantly reduced GFA values in the SLF III, AF, and FAT, compared with the siblings of individuals with ASD and TD boys [Amaral et al, ; Anagnostou & Taylor, ; Barnea‐Goraly & Hardan, ; Fletcher et al, ; Groen et al, ; Lo et al, ; Poustka et al, ; Shukla et al, ]. Our results imply that the altered tract integrity of these tracts might be associated with the social communication deficits of ASD.…”
Section: Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…Alteration of the FAT was also found in boys with ASD [Lo et al, ]. Consistent with previous reports, the present study found that the boys with ASD showed significantly reduced GFA values in the SLF III, AF, and FAT, compared with the siblings of individuals with ASD and TD boys [Amaral et al, ; Anagnostou & Taylor, ; Barnea‐Goraly & Hardan, ; Fletcher et al, ; Groen et al, ; Lo et al, ; Poustka et al, ; Shukla et al, ]. Our results imply that the altered tract integrity of these tracts might be associated with the social communication deficits of ASD.…”
Section: Discussionsupporting
confidence: 91%
“…The SMA that connects the IFG via the FAT has been associated with the impaired language and communication characteristics of ASD [Amaral, Schumann, & Nordahl, 2008]. Alteration of the FAT was also found in boys with ASD [Lo et al, 2017]. Consistent with previous reports, the present Table 3.…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations